2020
DOI: 10.3390/molecules25225474
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Nrf2 Signaling Pathway and Its Role in Inflammation

Abstract: Inflammation is a key driver in many pathological conditions such as allergy, cancer, Alzheimer’s disease, and many others, and the current state of available drugs prompted researchers to explore new therapeutic targets. In this context, accumulating evidence indicates that the transcription factor Nrf2 plays a pivotal role controlling the expression of antioxidant genes that ultimately exert anti-inflammatory functions. Nrf2 and its principal negative regulator, the E3 ligase adaptor Kelch-like ECH- associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
582
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 828 publications
(601 citation statements)
references
References 260 publications
(156 reference statements)
15
582
0
4
Order By: Relevance
“…Proof of the interaction and cooperative action of Nrf2 and NF-κB was taken from experimental work with various model systems employing plant extracts, individual compounds in vitro and in vivo, pure chemicals, and some known toxicants [ 6 ]. In our recent review, a central role of Nrf2 in antioxidant defenses and vitagene regulation was described in detail [ 27 ], and it seems likely that, under oxidative stress, the transcription factors NF-κB and Nrf2 antagonize each other to coordinate a stress response [ 60 , 67 , 76 ].…”
Section: Nrf2 and Nf-ĸb Interplay In Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…Proof of the interaction and cooperative action of Nrf2 and NF-κB was taken from experimental work with various model systems employing plant extracts, individual compounds in vitro and in vivo, pure chemicals, and some known toxicants [ 6 ]. In our recent review, a central role of Nrf2 in antioxidant defenses and vitagene regulation was described in detail [ 27 ], and it seems likely that, under oxidative stress, the transcription factors NF-κB and Nrf2 antagonize each other to coordinate a stress response [ 60 , 67 , 76 ].…”
Section: Nrf2 and Nf-ĸb Interplay In Oxidative Stressmentioning
confidence: 99%
“…Redox biology is a very quickly developing area of modern biological sciences, and roles of redox homeostasis in health and disease have recently received tremendous attention [ 1 , 2 , 3 , 4 , 5 , 6 ]. There are a range of redox pairs in cells/tissues responsible for redox homeostasis maintenance/regulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, accumulating evidence indicates that the transcription factor Nrf2 plays a pivotal role in regulating redox homeostasis by increasing antioxidant genes to maintain intracellular redox homeostasis. Nrf2 is known to stimulate the heme oxygenase-1 (HO-1) axis, which is a potent anti-inflammatory target [ 44 ]. It has been reported that DPP-4 inhibitors activate the Nrf2/HO-1 pathway [ 45 , 46 , 47 ].…”
Section: Mechanisms Underlying Renoprotection By Dpp-4 Inhibitorsmentioning
confidence: 99%
“…BNP is clinically used for the diagnosis and evaluation of CVD [ 69 ]. BNP is synthesized as a 134-amino acid precursor (prepro BNP) that is processed to proBNP [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , …”
Section: Dpp-4 Substratesmentioning
confidence: 99%